THE APPLICATION OF ELECTROSPRAY IONIZATION MASS SPECTROMETRY (ESI MS) TO THE STRUCTURAL CHARACTERIZATION OF NATURAL ORGANIC MATTER - Kujawinski E.B.; Freitas M.A.; Zang X.; Hatcher P.G.; Green-Church K.B.; Jones R.B. (My University, 2002)
This report describes the application of electrospray ionization (ESI) mass spectrometry to the structural characterization of soil organic material, a critical component of environmental processes and the global carbon cycle. Quadrupole time-of-flight (QqTOF) mass spectrometry provided a routine screening of aqueous ions in humic and fulvic acid mixtures and MS/MS capabilities for selected ions. Fourier transform ion cyclotron resonance (FT-ICR) mass spectrometry required longer analysis time but achieved resolving powers >80,000 and mass accuracies of <1 ppm, which allowed exact molecular formula determination for selected peaks. This technique represents a significant advance in the identification of compounds within humic substances.